Reproducibility of Ceftazidime/Avibactam MIC Results for Enterobacteriaceae and Pseudomonas aeruginosa Using MicroScan Dried Gram Negative MIC Panels. (4th October 2017) - Humphries, Romney; Hindler, Janet; Harrington, Amanda; DesJarlais, Sharon; Traczewski, Maria; Beasley, Denise; Brookman, Regina; Chau, Jennifer; Carpenter, Darcie
Abstract: Background: A multicenter study was performed to evaluate the reproducibility of Ceftazidime/Avibactam on a MicroScan Dried Gram Negative MIC (MSDGN) Panel. Materials/Methods: MSDGN panels were evaluated for reproducibility at three sites. For reproducibility, a total of 16 on-scale organisms were tested on MSDGN panels at each site (13 Enterobacteriaceae and 3 Pseudomonas aeruginosa ). Three replicates of each organism were tested each day for three days using the turbidity and PromptTM* methods of inoculation. MSDGN panels were incubated at 35 ± 2°C and read on the WalkAway System, the autoSCAN-4 instrument, and read visually. Read times for the MSDGN panels were at 16–20 hours. FDA breakpoints (µg/mL) used for interpretation of MIC results were: Enterobacteriaceae ≤ 8/4 S and ≥ 16/4 R; P. aeruginosa ≤ 8/4 S and ≥ 16/4 R. Results: Reproducibility among the three sites was greater than 95% for all read methods for both the turbidity and Prompt inoculation methods. Conclusion: This multicenter study showed that Ceftazidime/Avibactam MIC results for Enterobacteriaceae and P. aeruginosa obtained with the MSDGN panel are highly reproducible. * PROMPT is a registered trademark of 3M. Beckman Coulter, the stylized logo and the Beckman Coulter product and service marks mentioned herein are trademarks or registered trademarks of Beckman Coulter, Inc. in the United States and other countries. Pending clearance by US FDA, CE compliance, and other regulatory registrations. Disclosures: All authors: No reported disclosures.